Meta-Analysis of Renal Replacement Therapy for Burn Patients: Incidence Rate, Mortality, and Renal Outcome - Duan, ZhiYu; Cai, GuangYan; Li, JiJun; Chen, FengKun; Chen, XiangMei (Frontiers in Medicine, 2021)
Background: Renal replacement therapy (RRT) was often needed by some severe burn patients with acute kidney injury (AKI). The primary aim of this study was to review incidence rate and mortality of RRT in severe burn patients. Second aims were to review RRT complications and renal outcome. Methods: We searched multiple databases for studies published between 1 January 1960 and 31 December 2019. Studies about adult populations with burn injury, providing epidemiologic data on prevalence or mortality of RRT, were included. Results: A total of selected 57 studies, including 27,437 patients were enrolled in our analysis. The prevalence rates of RRT were 8.34% (95%CI 7.18%-9.5%) in all burn patients and 37.05% (95%CI 29.85%-44.24%) in AKI patients. The mortality of all burn patients with RRT was 65.52% (95%CI 58.41%-72.64%). The prevalence rates of RRT in sample size≥100 group were 6.86% (95%CI 5.70%-8.03%), which was lower than that of <100 group (17.61%, 95%CI 13.39%-21.82%). With the increase of TBSA, the prevalence of RRT may have the increasing trend. The prevalence rates of RRT in Asian group was 12.75% (95%CI 9.50%-16.00%), which was higher than that of European (10.45%, 95%CI 7.30%-13.61%) and North America group (5.61%, 95%CI 4.27%-6.95%). The prevalence rates of RRT in 2010-2019 group was 12.22% (95%CI 10.09%-14.35%), which was higher than that of 2009-2000 group (5.17%, 95%CI 2.88%-7.46%). The prevalence rates of RRT in 1989 and before group was the lowest, which was 1.56% (95%CI 0%-3.68%). However, there was no significant correlation between the year of publication and the mortality of burn patients with RRT. Dialysis-requiring AKI in burn patients could increases the risk of chronic kidney disease progression and end-stage renal disease. About 35% of RRT patients need to maintain haemodialysis temporarily, even if they survive and leave hospital. Conclusions: The prevalence rate of RRT is about 6-8%; approximately, one-third of burn patients with AKI need RRT. The prevalence rate of RRT increased over time, but the mortality did not change. The prevalence rates of RRT in Asian group was higher than that of European and North America group.